Kajian Literatur Perilaku Leaching dan Abrasi pada Beton Berpori: indonesia - Hidayat, Khoirul Fatah; Kamulyan, Budi; Supraba, Intan (Asian Journal of Innovation and Entrepreneurship, 2025)
The durability of pervious concrete is threatened by the phenomena of leaching (chemical dissolution) and abrasion (mechanical wear). This systematic literature review analyzes studies from Scopus (2019–2024), utilizing keywords such as “pervious concrete” or “porous concrete”, “leaching”, and “abrasion”. Articles were selected based on open access, peer-review status, and relevance to experimental/theoretical data. Leaching, primarily driven by the dissolution of calcium from portlandite and C-S-H phases, weakens the cement matrix and increases porosity. Meanwhile, abrasion is physical wear resulting from mechanical forces that erode the cement paste and lead to aggregate dislodgement. Critically, leaching and abrasion interact synergistically in a self-reinforcing degradation cycle: leaching weakens the matrix, making it more susceptible to abrasion, while abrasion exposes fresh material, accelerating further leaching. Although material optimization (e.g., angular aggregates and silica fume additives) and controlled carbonation curing can mitigate degradation, significant research gaps persist. Notably, there is a lack of systematic investigation to optimize cement-aggregate ratios for simultaneous leaching and abrasion resistance, as well as a scarcity of standardized coupled degradation test protocols. To address this gap, a systematic investigation is needed to optimize the sand-to-cement ratio in concrete filters, balancing durability (including resistance to fluid friction during backwashing) with sustained filtration capacity. This is crucial for developing pervious concrete as a sustainable and durable urban solution.